2021
DOI: 10.3389/fnut.2021.762929
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotics for the Treatment of Docetaxel-Related Weight Gain of Breast Cancer Patients—A Single-Center, Randomized, Double-Blind, and Placebo-Controlled Trial

Abstract: Background: Docetaxel is an important chemotherapy-agent for breast cancer treatment. One of its side-effects is weight gain, which increases the all-cause mortality rate. Considering gut microbiota is one important factor for weight regulation, we hypothesized that probiotics could be potentially used to reduce the docetaxel-related weight gain in breast cancer patients.Methods: From 10/8/2018 to 10/17/2019, 100 breast cancer (Stage I-III) patients underwent four cycles of docetaxel-based chemotherapy were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…However, B6MNI was the sole treatment that enhanced IgA in the colon of female mice, while having no effect on IgA synthesis in the jejunum or ileum. This finding may be explained by strain variations and intestinal niches [ 47 ]. Furthermore, B6MNI was isolated from human breastmilk, whereas the remaining seven strains were obtained from the feces of infants.…”
Section: Discussionmentioning
confidence: 99%
“…However, B6MNI was the sole treatment that enhanced IgA in the colon of female mice, while having no effect on IgA synthesis in the jejunum or ileum. This finding may be explained by strain variations and intestinal niches [ 47 ]. Furthermore, B6MNI was isolated from human breastmilk, whereas the remaining seven strains were obtained from the feces of infants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, probiotic supplementation leads to stabilized body fat, reduced metabolic changes and attenuated gut dysbacteriosis during docetaxel-based chemotherapy of breast cancer patients 111 . More recently, breast cancer patients who have undergone chemotherapy were subjected to a 12-week exercise regime.…”
Section: Restoring the Gut Microbiota As An Effective Therapeutic Str...mentioning
confidence: 99%
“…Both studies reported no difference in microbial diversity between the two groups. The first study revealed that probiotic administration during docetaxel-based chemotherapy was associated with stable weight, body fat, glucose, total cholesterol, and low-density lipoprotein (LDL) [22].…”
Section: Modulation By Probiotics and Antibioticsmentioning
confidence: 99%
“…Juan et al conducted two randomized controlled trials which aimed to determine differences in fecal microbiota and incidence of side effects between patients who received a probiotic supplement or placebo during chemotherapy [ 21 , 22 ]. Both studies reported no difference in microbial diversity between the two groups.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation